«The Russian View on History» - Nikolay Ivanovich Bezlepkin (Управленческое консультирование, 2018)
In the article features of formation and development of university philosophy of history in Russia of the middle of XIX - the beginnings of the 20th centuries are analyzed. Were characteristic of it: indissoluble communication with traditions of a domestic historiosophy, domination of ontological approach in research of historical process, and the original solution of a question of a ratio of the world and national history. In the set these features made, according to T. N. Granovsky, an essence of “the Russian view on history” which has been the basis for teaching at the Russian Universities during the considered period.